Співпраця Вадима Модзалевського та Володимира Міяковського в галузі архівного будівництва доби Української революції (1918–1920) - Борщ, І. (Архіви України, 2008)
The article deals with creative cooperation of two well-known Ukrainian scientists in the area of archival affairs development in Ukraine in 1918-1920, undertakes the analysis of their attitudes towards archival affairs development, their common features and differences.